Pooled analysis of the surgical treatment for colorectal cancer liver metastases. Issue 1 (April 2015) - Veereman, G.; Robays, J.; Verleye, L.; Leroy, R.; Rolfo, C.; Van Cutsem, E.; Bielen, D.; Ceelen, W.; Danse, E.; De Man, M.; Demetter, P.; Flamen, P.; et al.
Highlights In colorectal cancer patients with liver metastases resection should always be attempted. In case of synchronous metastases overall survival is not affected by timing of surgery (concomitant vs. staged). In case of synchronous metastases in a fit patient, concomitant resection may result in lower postoperative morbidity. Systemic peri-operative or adjuvant chemotherapy may improve progression free survival. Overall survival is not affected by the use of adjuvant chemotherapy.